Approximating Characteristics of the Analogs of Besov Classes with Logarithmic Smoothness - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We obtain the exact-order estimates of some approximating characteristics for the analogs of Besov classes of periodic functions of several variables (with logarithmic smoothness).